Antimicrobial susceptibility testing of pathogens isolated from blood culture: a performance comparison of Accelerate Pheno™ and VITEK® 2 systems with the broth microdilution method. (25th January 2019) - De Angelis, Giulia; Posteraro, Brunella; Menchinelli, Giulia; Liotti, Flora Marzia; Spanu, Teresa; Sanguinetti, Maurizio
Abstract: Objectives: To compare the performance of the Accelerate Pheno™ system with that of the conventional phenotypic VITEK ® 2 system for rapid antimicrobial susceptibility testing (AST) of bacterial pathogens from positive blood culture (PBC) samples, based on the reference broth microdilution (BMD) method. Methods: Prospectively collected PBCs that represented patient-unique bloodstream infection episodes were included. For PBC samples showing monomicrobial growth ( n = 86), AST was performed using both Accelerate Pheno™ and VITEK ® 2 systems directly from PBC broth. Colony isolates derived from subculture of PBC broth were then used for BMD testing. AST results were interpreted according to 2017 EUCAST breakpoints. Results: The overall categorical agreement between Accelerate Pheno™ system and BMD was 92.7% (467/504) for Gram-negative organisms and 99.0% (95/96) for Gram-positive organisms, with rates for very major errors of 3.6% (6/166), major errors 2.2% (9/416) and minor errors 3.8% (23/600). The overall categorical agreement between the VITEK ® 2 system and BMD was 91.7% (463/505) for Gram-negative organisms and 99.0% (97/98) for Gram-positive organisms, with rates of very major errors of 2.4% (4/169), major errors 1.0% (4/416) and minor errors 5.8% (35/603). Importantly, unlike the VITEK ® 2 system, no false-susceptible results occurred with two colistin-resistant organism-growing PBCs tested using the Accelerate Pheno™ system. Conclusions: Based on these findings, the Accelerate Pheno™ system can be a valid alternative for the rapid AST of Gram-negative and Gram-positive bacteria in bloodstream infections.